Vitamin B12 deficiency in the brain leads to DNA hypomethylation in the TCblR/CD320 knockout mouse - Fernàndez-Roig Sílvia; Lai Shao-Chiang; Murphy Michelle M; Fernandez-Ballart Joan; Quadros Edward V (Nutrition & Metabolism, 2012)
Abstract Background DNA methylation is an epigenetic phenomenon that can modulate gene function by up or downregulation of gene expression. Vitamin B12 and folate pathways are involved in the production of S-Adenosylmethionine, the universal methyl donor. Findings Brain vitamin B12 concentration and global DNA methylation was determined in transcobalamin receptor (TCblR/CD320) knock out (KO) (n = 4) and control mice (n = 4) at 20–24 weeks of age. Median [IQR] brain vitamin B12 concentrations (pg/mg) in TCblR/CD320 KO mice compared with control mice was 8.59 [0.52] vs 112.42 [33.12]; p < 0.05. Global DNA methylation levels in brain genomic DNA were lower in TCblR/CD320 KO compared with control mice (Median [IQR]: 0.31[0.16] % vs 0.55[0.15] %; p < 0.05.). Conclusions In TCblR/CD320 KO mice, brain vitamin B12 drops precipitously by as much as 90% during a 20 week period. This decrease is associated with a 40% decrease in global DNA methylation in the brain. Future research will reveal whether the disruption in gene expression profiles due to changes in DNA hypomethylation contribute to central nervous system pathologies that are frequently seen in vitamin B12 deficiency.